In work, at home : towards an understanding of homeworking - Felstead, Alan, 1963-; Jewson, Nick, 1946- (London ; New York : Routledge, 2000)
More and more people are choosing to earn a living at home. In Work, At Home explores the meaning and experience of this type of employment by covering a wide range of issues including:* social relationships* current research methodologies* statistical analyses of global labour markets* the emotional and psychological processes of self-management* home relations. Presenting statistical analyses of labour markets in North America, Europe, Asia and Australia, In Work, At Home provides a valuable introduction to the issues and debates surrounding homeworki.
Chapter 1 Introduction: setting the agenda -- Setting the agenda The field of enquiry -- chapter 2 Conceptualising the field -- chapter 3 Searching for subjects -- chapter 4 Taking a count -- chapter 5 Revealing diversity -- chapter 6 Documenting the grim realities -- chapter 7 Struggling for control -- chapter 8 Managing the self -- chapter 9 Combining home and work -- chapter 10 Conclusion -- Mapping the broader perspective.
Includes bibliographical references (pages 182-196) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Self-employed -- United States; Self-employed.; Home labor -- United States; Home labor; Home-based businesses -- United States; Home-based businesses; Cottage industries -- United States; Cottage industries; Travailleurs indépendants -- États-Unis.; Travailleurs indépendants.; Travail à domicile -- États-Unis.; Travail à domicile; Entreprises établies à domicile -- États-Unis.; Entreprises établies à domicile; Industrie familiale -- États-Unis.; Industrie familiale; cottage industries; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Cottage industries; Home-based businesses; Home labor; Self-employed; United States; Heimarbeit; Thuiswerk; Huisindustrie; Economische aspecten; Psychologische aspecten